Gas in Russian-German Economic and Political Relations - Svobodová, Alena (2013)
The purpose of this work is to analyze the role of natural gas in Russian-German political and economic relations. A macroeconomic analysis, with focus on commodity and territorial structure of international trade of both countries, provides a framework of Russian-German bilateral relations. The work shows that natural resources give Russia a strong political leverage in international politics as was illustrated in the past on the Ukrainian gas crisis in 2009. Germany is to a great extent dependent on Russian gas and therefore, in order to improve energy security, attempts to diversify its suppliers and supply routes of natural gas. These efforts have been so far unsuccessful and therefore, the nature of energy interdependence between Russia and Germany was determined. The work also looks at potential future developments of this interdependence by examining influencing factors.